Using book talks and choice to increase reading motivation - Homan, Jessica Suter (My University, 2015)
The purpose of this action research was to show how book talks and student choice can have an impact on students' motivation to read. A book talk is when a teacher or student tells the class a little bit about the book in order to get them interested to read it on their own. Analysis of the qualitative and quantitative data revealed that eight of the eleven students who participated in this study increased their reading motivation, while the other three remained the same. Furthermore, all of the students enjoyed having one day per week designated for book talks and choice reading and recommended that it continue as a part of the intervention block. In order for students to sustain a lifelong love of reading, they need to be intrinsically motivated to read. This study demonstrated that intrinsic motivation can be developed through book talks and allowing students to select their reading materials. For teachers to motivate students, they must be responsive to the different literacy personalities that each student brings to the classroom. In addition, teachers can contribute to reading engagement when they share their passions and struggles about reading with students.
Plan B Paper. 2015. Master of Science in Education- Reading--University of Wisconsin-River Falls. Teacher Education Department. 26 leaves. Includes bibliographical references (leaves 20-21).
Keywords: Reading (Elementary); Book talks; Motivation in education